EXPERIMENTAL INQUIRY OF PUPPETS AND VIDEO ON STUDENTS’ SPEAKING SKILL OF TRANSACTIONAL AND INETRPERSONAL EXPRESSIONS - Batdal Niati (JEE (Journal of English Education), 2016)
This research was intended to investigate whether students who were taught by puppets had better speaking skill of transactional and interpersonal expression than those who were taught by video. This research was experimental research; nonrandomized control group prepost test design. The treatments were done in both of classes; experimental I and experimental II class. Experimental I was taught by puppets while experimental II class was taught by video. Instrument used to collect the data was speaking test. Independent t-test was chosen to analyze data. Finding showed that students who were taught by puppets had better speaking skill of transactional and interpersonal expression than those who were taught by video. Puppets enhanced students’ gain score of speaking skill.